Application of Acoustic Emission on the Characterization of Fracture in Textile Reinforced Cement Laminates - J. Blom; J. Wastiels; D. G. Aggelis (The Scientific World Journal)
This work studies the acoustic emission (AE) behavior of textile reinforced cementitious (TRC) composites under flexural loading. The main objective is to link specific AE parameters to the fracture mechanisms that are successively dominating the failure of this laminated material. At relatively low load, fracture is initiated by matrix cracking while, at the moment of peak load and thereafter, the fiber pull-out stage is reached. Stress modeling of the material under bending reveals that initiation of shear phenomena can also be activated depending on the shape (curvature) of the plate specimens. Preliminary results show that AE waveform parameters like frequency and energy are changing during loading, following the shift of fracturing mechanisms. Additionally, the AE behavior of specimens with different curvature is very indicative of the stress mode confirming the results of modeling. Moreover, AE source location shows the extent of the fracture process zone and its development in relation to the load. It is seen that AE monitoring yields valuable real time information on the fracture of the material and at the same time supplies valuable feedback to the stress modeling.